Real‐world efficacy and toxicity of combined nivolumab and ipilimumab in patients with metastatic melanoma. Issue 1 (13th November 2018) - Parakh, Sagun; Randhawa, Manreet; Nguyen, Bella; Warburton, Lydia; Hussain, Mohammad Akhtar; Cebon, Jonathan; Millward, Michael; Yip, Desmond; Ali, Sayed
Abstract: Background: There is limited real‐world data on the efficacy and safety of combination programmed cell death protein‐1 (PD‐1) inhibitor, nivolumab and the cytotoxic T‐lymphocyte antigen (CTLA‐4) inhibitor ipilimumab. Method: We retrospectively identified patients (pts) with metastatic melanoma treated with three‐weekly nivolumab (1 mg/kg) in combination with ipilimumab (3 mg/kg) for four cycles followed by nivolumab monotherapy (3 mg/kg) fortnightly. Patient demographics and treatment parameters were collected and outcomes determined. Results: A total of 45 pts received combination treatment with a median follow up of 8.7 months (range 0.33–25.9 months). A total of 67% were male, and BRAF V600 mutations detected in 38%. At treatment commencement, 14 (31%) pts had brain metastases, 51% had an elevated LDH and 18 (40%) were treatment‐naive. Almost a third (30%) required corticosteroids for symptom control or management of prior toxicities. Nineteen (42%) patients had prior anti‐PD‐1 therapy. The disease control rate (DCR) was 54% and objective response rate (ORR) was 29%. Of pts treated with prior immune checkpoint inhibitors, the DCR and ORR were 50% and 33%, respectively. Intracranial responses were observed in 18% ( n = 2). The median progression‐free survival (PFS) was 5.8 months (95% Confidence interval (CI), 2.9–14.1 months). PFS was higher in treatment naïve patients compared to those who had prior immunotherapy (6.2 months vs 4.9 months, P = 0.59). The median OS was 17.4 months (95% CI, 7.1–NR). pts requiring corticosteroids had a shorter PFS (4.9 months vs 6.8 months) and OS (7.1 months vs NR, P = 0.01).Treatment‐related adverse events of any grade were experienced by 88% of pts, with 54% having grade 3–4 adverse events. Treatment discontinuation due to adverse events occurred in 44% of pts. Conclusion: In this study, responses to combination immunotherapy were lower than reported. Patients treated with prior immunotherapy had similar responses as treatment‐naïve pts. The toxicity profile seen in this study is similar to those reported in clinical trials.